Braille preservation: recognising and respecting archival materials produced by and for the blind - Lisa J Sisco (Archives & Manuscripts, 2015)
There is a noticeable gap in the archival literature concerning the preservation of braille and other tactile print formats that, since the eighteenth century, have been produced by and for blind and visually impaired persons. Based on the insights gained from interviews with information professionals and additional research conducted by the author into the historical usage and production of braille, this paper aims to highlight factors that may affect the preservation and accessibility of braille in archives. While this article will not generate specific preservation guidelines, policies and procedures for braille – measures to be created in a future study – the purpose of this article is to draw an initial awareness to the issues that influence the preservation of and access to these archival records.